Technical, Economic And Sustainability Considerations Of A Solar Pv Mini Grid As A Tool For Rural Electrification In Uganda - Bakkabulindi, Geofrey; Sendegeya, Al-Mas; Silva, Izael Da; Lugujjo, Eriabu (Bakkabulindi, G., Sendegeya, A., Da Silva, I., & Lugujjo, E. (2010, July), 2010)
The challenges facing rural electrification in Uganda are diverse with less than 3% of the rural population having access to electricity. The establishment of mini-grids powered by renewable energy sources makes it possible to electrify remote areas at affordable rates. In this study, an assessment of a solar PV mini-grid system to provide electricity to forty households in rural Uganda was carried out. The considered system comprised six solar modules each rated 175 Wp, a controller, off-grid inverter and batteries with a capacity of 600 Ah. Manufactured by SMA, the Sunny Island inverter proposed for the mini-grid would ensure provision of grid-quality electricity. The study aimed to investigate the mini-grid’s technical design with focus on optimal distribution against constraints of voltage drops, electrical losses and increasing load. Customised load limiters shared between households using thermistors were included to reduce costs and limit consumption. The incomes of rural households are often seasonal and thus issues pertaining to affordability and sustainability were also considered. Results of the economic analysis showed a payback period of less than 5 years given an affordable fixed monthly tariff for the case study area.
Keywords: Mini-grid, Photovoltaics (PV), rural electrification